Controlled weakening of model ice: Replicating the mechanical response of summer-warmed sea ice in laboratories and test basins - N. Fuchs; F. von Bock und Polach; P. Buil; S.M. Isay; D. Notz; L. Nupnau; N. Reimer; L. Schoepflin; T. Zorn (Ocean Engineering, 2026)

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

The grapevine Vitis shuttleworthii accession D’Arpa reveals resistance against Xiphinema index in an inoculation screening assay - F. Fuchs; J. Schurig; M. Nicklas; A. Baßler; O. Trapp; P. Winterhagen (European Journal of Plant Pathology, 2026)
The Grapevine fanleaf virus (GFLV) transmitted by the vector nematode Xiphinema index causes severe losses in viticulture. Truly resistant rootstocks that inhibit nematode development and virus transmission to grapevines are not available. Seedlings with genetic background of the accession Vitis shuttleworthii D’Arpa were evaluated using an established screening system to test for nematode resistance. For all tested candidate grapevines it turned out that reproduction and fertility of X. index was strongly reduced compared to the susceptible control rootstock Selektion Oppenheim (SO4) and similar to the partly resistant reference rootstock Nemadex Alain Bouquet. GFLV infection was identified on controls and references after inoculation with viruliferous nematodes, but virus was not detected in any of the candidate genotypes with D’Arpa background. Results indicate that D’Arpa contains resistance traits, which may be interesting for breeding nematode resistant rootstocks.

Toxic food: commercial bear meat products are highly contaminated with lead (Pb) from hunting ammunition - Jon M. Arnemo; Adam F. G. Leontowich; Boris Fuchs; Helle B. Hydeskov; Ilia Rodushkin; Samantha Totoni; Cora Paulukat; Jordan O. Hampton (Exposure and Health, 2026)

Video-assisted ovarian sterilization by occluding the vascular supply with a modified Miller's knot and performing bilateral partial excision of the ovaries in the red-eared slider turtle (Trachemys scripta elegans) - Luis Baselly-Cueva; Diego A. Ospina-Argüelles; Luan Sitó-Silva; Beatriz Lippe de Camillo; Kárita da Mata Fuchs; Alessandra Dhom Pimentel de Moraes; Vania Maria de Vasconselos Machado; Paulo Fernandes Marcusso; Carlos González-Zambrano; Luís F. Barbisan; David Javier Galindo; Luis Mauricio Montoya Florez; et al. (The Veterinary Journal, 2026)

Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

Antibacterial Synergism of Fluoxetine and Paroxetine with Ceftriaxone, Plasmid DNA Cleavage and Repositioning - Vitória S. Foletto; Marissa B. Serafin; Augusto D. da Mota; Taciéli F. da Rosa; Angelita Bottega; Sara L. Marion; Bruno R. de Paula; Laísa N. Franco; Luana B. Fuchs; Rosmari Hörner (Current Microbiology, 2025)

Does ‘portion size’ matter? Brain responses to food and non-food cues presented in varying amounts - Bari A. Fuchs; Alaina L. Pearce; Barbara J. Rolls; Stephen J. Wilson; Emma Jane Rose; Charles F. Geier; Kathleen L. Keller (Appetite, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Repositioning of Benzodiazepine Drugs and Synergistic Effect with Ciprofloxacin Against ESKAPE Pathogens - Taciéli F. da Rosa; Marissa B. Serafin; Vitória S. Foletto; Laísa N. Franco; Bruno R. de Paula; Luana B. Fuchs; Luciano Calegari; Rosmari Hörner (Current Microbiology, 2023)

A desiccated dual-species subaerial biofilm reprograms its metabolism and affects water dynamics in limestone - F. Villa; N. Ludwig; S. Mazzini; L. Scaglioni; A.L. Fuchs; B. Tripet; V. Copié; P.S. Stewart; F. Cappitelli (Science of The Total Environment, 2023)

Miscibility in systems containing (poly(oxymethylene) ethers (OME) + hydrocarbons + water) - Christian F. Breitkreuz; Alexander Holzer; Thorsten Fuchs; Michael Günthner; Hans Hasse (Fuel, 2023)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Endogenous anandamide and self-reported pain are significantly reduced after a 2-week multimodal treatment with and without radon therapy in patients with knee osteoarthritis: a pilot study - M. Gaisberger; J. Fuchs; M. Riedl; S. Edtinger; R. Reischl; G. Grasmann; B. Hölzl; F. Landauer; H. Dobias; F. Eckstein; M. Offenbächer; M. Ritter; et al. (International Journal of Biometeorology, 2021)
Multimodal therapies comprising spa applications are widely used as non-pharmaceutical treatment options for musculoskeletal diseases. The purpose of this randomized, controlled, open pilot study was to elucidate the involvement of the endocannabinoid system in a multimodal therapy approach. Twenty-five elderly patients with knee osteoarthritis (OA) received a 2-week spa therapy with or without combination of low-dose radon therapy in the Bad Gastein radon gallery. A 10-point numerical rating scale (pain in motion and at rest), WOMAC questionnaire, and the EuroQol-5D (EQ-5D) questionnaire were recorded at baseline, and during treatment period at weeks one and two, and at 3-month and 6-month follow-ups. Plasma levels of the endocannabinoid anandamide (AEA) were determined at baseline and at 2 weeks, and serum levels of several cartilage metabolism markers at all five time-points. A significant and sustained reduction of self-reported knee pain was observed in the study population, but no further significant effect of the additional radon therapy up and above base therapy. This pain reduction was accompanied by a significant reduction of AEA plasma levels during treatment in both groups. No significant differences were seen in serum marker concentrations between the groups treated with or without radon, but a small reduction of serum cartilage degradation markers was observed during treatment in both groups. This is the first study investigating AEA levels in the context of a non-pharmacological OA treatment. Since the endocannabinoid system represents a potential target for the development of new therapeutics, further studies will have to elucidate its involvement in OA pain.

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

The Arnon–Buchanan cycle: a retrospective, 1966–2016 - Bob B. Buchanan; Reidun Sirevåg; Georg Fuchs; Ruslan N. Ivanovsky; Yasuo Igarashi; Masaharu Ishii; F. Robert Tabita; Ivan A. Berg (Photosynthesis Research, 2017)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Capulavirus and Grablovirus: two new genera in the family Geminiviridae - Arvind Varsani; Philippe Roumagnac; Marc Fuchs; Jesús Navas-Castillo; Enrique Moriones; Ali Idris; Rob W. Briddon; Rafael Rivera-Bustamante; F. Murilo Zerbini; Darren P Martin (Archives of Virology, 2017)

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Genetic characterization and barcoding of taxa in the genera Landoltia and Spirodela (Lemnaceae) by three plastidic markers and amplified fragment length polymorphism (AFLP) - Manuela Bog; Ulrich Lautenschlager; Maria F. Landrock; Elias Landolt; Joerg Fuchs; K. Sowjanya Sree; Christoph Oberprieler; Klaus-J. Appenroth (Hydrobiologia, 2015)

Rediscovering ACE: novel insights into the many roles of the angiotensin-converting enzyme - Romer A. Gonzalez-Villalobos; Xiao Z. Shen; Ellen A. Bernstein; Tea Janjulia; Brian Taylor; Jorge F. Giani; Wendell-Lamar B. Blackwell; Kandarp H. Shah; Peng D. Shi; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2013)

A structured approach to enhance flood hazard assessment in mountain streams - B. Mazzorana; F. Comiti; S. Fuchs (Natural Hazards, 2013)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Identifying sites of saccade amplitude plasticity in humans: transfer of adaptation between different types of saccade - J. Johanna Hopp; Albert F. Fuchs (Experimental Brain Research, 2010)

Evidence for distinct populations of human Merkel cells - A.-C. Eispert; F. Fuchs; J. M. Brandner; P. Houdek; E. Wladykowski; Ingrid Moll (Histochemistry and Cell Biology, 2009)

Chemical composition of tourmaline from the Asarcık Pb–Zn–Cu ± U deposit, Şebinkarahisar, Turkey - F. Yavuz; Y. Fuchs; N. Karakaya; M. Ç. Karakaya (Mineralogy and Petrology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Transferrin recycling and dextran transport to lysosomes is differentially affected by bafilomycin, nocodazole, and low temperature - Gnther Baravalle; Daniela Schober; Marlis Huber; Nora Bayer; Robert F. Murphy; Renate Fuchs (Cell and Tissue Research, 2005)

Exploring the method of optical dating and comparison of optical and 14 C ages of Late Weichselian coversands in the southern Netherlands - D. Vandenberghe; C. Kasse; S. M. Hossain; F. De Corte; P. Van Den Haute; M. Fuchs; A. S. Murray (Journal of Quaternary Science, 2004)
A study was made of the applicability of three different techniques for equivalent dose ( D e ) determination in the optical dating of quartz: the single‐aliquot regenerative‐dose technique (SAR), the single‐aliquot additive‐dose technique (SAAD) and the multiple‐aliquot additive‐dose technique (MAAD). For this purpose, quartz grains were extracted from a sequence of Upper Pleniglacial to Late‐glacial coversands exposed at the locality of Ossendrecht in the southwestern Netherlands, a site for which both radiocarbon and earlier luminescence dates are available, providing independent age control. Upon testing the different assumptions underlying each of the three OSL techniques investigated, the SAR protocol was found to be the technique of choice. The optical ages obtained with this protocol were in good agreement with the chronostratigraphical position of the sediments investigated and with the available chronostratigraphical information on the same and equivalent deposits. This confirms the suitability of the SAR technique for dating coversands. Furthermore, a small laboratory intercomparison of SAR‐based D e determinations yielded results that were in fair overall agreement. Copyright © 2004 John Wiley & Sons, Ltd.

Investigating the site of human saccadic adaptation with express and targeting saccades - J. Johanna Hopp; Albert F. Fuchs (Experimental Brain Research, 2002)

MouseNet© database: digital management of a large-scale mutagenesis project - Walter Pargent; Stephan Heffner; Karlheinz F. Schäble; Dian Soewarto; Helmut Fuchs; Martin Hrabé de Angelis (Mammalian Genome, 2000)

A 500-kb region on chromosome 16p13.1 contains the pseudoxanthoma elasticum locus: high-resolution mapping and genomic structure - Li Cai; Berthold Struk; Mark D. Adams; Wan Ji; Thomas Haaf; Hyung-Lyun Kang; So Hee Dho; Xuequn Xu; Franziska Ringpfeil; Julie Nancarrow; Stéphanie Zäch; Lori Schaen; et al. (Journal of Molecular Medicine, 2000)

Flexibility of saccade adaptation in the monkey: different gain states for saccades in the same direction - Shoji Watanabe; Christopher T. Noto; Albert F. Fuchs (Experimental Brain Research, 2000)

Scales of Heterogeneities in the Continental Crust and Upper Mantle - M. Tittgemeyer; F. Wenzel; T. Ryberg; K. Fuchs (Pure and Applied Geophysics, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Evolution of extreme polyandry in the honeybee Apis mellifera L. - S. Fuchs; R. F. A. Moritz (Behavioral Ecology and Sociobiology, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Anaerobic metabolism of 2-hydroxybenzoic acid (salicylic acid) by a denitrifying bacterium - C. F. C. Bonting; Georg Fuchs (Archives of Microbiology, 1996)

Anaerobic degradation of m -cresol via methyl oxidation to 3-hydroxybenzoate by a denitrifying bacterium - C. F. C. Bonting; Sabine Schneider; Gü nther Schmidtberg; Georg Fuchs (Archives of Microbiology, 1995)

Anaerobic degradation ofm-cresol via methyl oxidation to 3-hydroxybenzoate by a denitrifying bacterium - Cornelus F. C. Bonting; Sabine Schneider; Günther Schmidtberg; Georg Fuchs (Archives of Microbiology, 1995)

Gametic differentiation in Chlamydomonas reinhardtii: light dependence and gene expression patterns - Ulrike Treier; Sabine Fuchs; Martina Weber; Warren W. Wakarchuk; Christoph F. Beck (Archives of Microbiology, 1989)

Lithoautotrophic growth of sulfate-reducing bacteria, and description of Desulfobacterium autotrophicum gen. nov., sp. nov. - K. Brysch; C. Schneider; G. Fuchs; F. Widdel (Archives of Microbiology, 1987)

Carbon assimilation pathways in sulfate-reducing bacteria II. Enzymes of a reductive citric acid cycle in the autotrophic Desulfobacter hydrogenophilus - R. Schauder; F. Widdel; G. Fuchs (Archives of Microbiology, 1987)

Introduction and establishment ofApanteles flavipes [Hym.: Braconidae] onDiatraea saccharalis [Lep.: Pyralidae] in texas - T. W. Fuchs; F. R. Huffman; J. W. Smith (BioControl, 1979)

Bacterial breakdown of benomyl. II. Mixed cultures - A. Fuchs; F. W. de Vries (Antonie van Leeuwenhoek, 1978)

Bacterial breakdown of benomyl. I. Pure cultures - A. Fuchs; F. W. de Vries (Antonie van Leeuwenhoek, 1978)